Isoflavone content and antioxidant activity of Thai fermented soybean and its capsule formulation - Chaiyavat Chaiyasut (2018)
Soybeans (Glycine max) are usually eaten as processed foods. Fermented soybeans are among the most popular of these processed foods. The aim of this study was to determine the effect of fermentation duration on isoflavone content and antioxidant activity of fermented soybeans. Capsule formulation of fermented soybeans was also studied. The Thai soybean variety, Rajamangala60, was fermented with Aspergillus oryzae. Isoflavone content and antioxidant activity were studied at 0, 12, 18, 36, 48, 96, 120, 168, 240, 360 and 480 h of fermentation duration. The results showed that isoflavone glycones (daidzin and genistin) decreased during fermentation, but aglycones (daidzein and genistein) increased. The highest amount of isoflavone aglycones was 384.30 ± 4.60 and 116.50 ± 1.56 mg/100 g fermented soybeans for daidzein and genistein, respectively. Antioxidant activity of fermented soybeans was evaluated by ABTS cation radical scavenging and ferric reducing antioxidant power (FRAP) methods. Antioxidant activity of fermented soybeans is increased during fermentation. Increases in isoflavone aglycones content and antioxidant activity were related to fermentation duration. The highest antioxidant activity of fermented soybean was found at the 240 h of fermentation with trolox equivalent antioxidant capacity (TEAC) 1.98 ± 0.09 μg trolox/g fermented soybean and FRAP value of 0.623 ± 0.002 μg FeSO4/g fermented soybean. Soybeans fermented for 240 h were then formulated as capsules by a wet granulation method. They were then assessed for appearance, weight variation, disintegration time and antioxidative properties. The results showed that fermented soybean capsules conformed to USP32/NF27 criteria on weight variation and disintegration. Their antioxidant activity was lower than 240 h fermented soybeans, but still higher than the non-fermented ones (p <0.05). © 2010 Academic Journals.